Grain sizes of sand substrates significantly influence the growth, survival, digestive enzyme profiles, and gut histology of sandfish (Holothuria scabra Jaeger 1833) juveniles during cultivation - Sari Budi Moria Sembiring; Rarastoeti Pratiwi; Suwarno Hadisusanto; Ketut Mahardika; Haryanti Haryanti; Jhon Harianto Hutapea (Aquaculture Reports)
This study aimed to determine suitable sand grain sizes as substrates for rearing sandfish juveniles. Twelve containers, 59 cm× 47 cm x 37 cm, and 30 juveniles were put into each as experimental animals. The initial mean wet weight of juveniles was 2.22 ± 0.43 g. Treatments were different sand grain sizes as substrates: small, medium, large, and without substrate as a control. Juveniles were fed with benthos at 2 % of daily biomass for 90 days. Specific growth and survival rates, enzyme activities, and intestine profiles were measured. The final mean weight of the juveniles in small, medium, and large sand grains sizes and control were 5.85 ± 0.52 g, 4.00 ± 0.37 g, 3.74 ± 0.45 g, and 3.69 ± 0.43 g, respectively. Small sand grain sizes show The fastest growth rate (P < 0.05). Survival rates between sand grain size treatments and control were significantly different (P < 0.05). The small sand grain sizes treatment showed the highest enzyme activity and longest villi sizes compared to other treatments and controls. Small sand grain sizes as the substrate are ideal for growing juvenile sandfish by optimizing the enzyme activities and allowing villi to absorb more food.